2000
DOI: 10.1007/s004499900177
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen availability and growth of Escherichia coli W3110: Dynamic responses to limitation and starvation

Abstract: It is well known that oxygen availability can have a profound effect upon the growth of an Escherichia coli culture with respect to acetate excretion or lower product yield. The current investigation seeks to determine the dynamic responses of steady state continuous cultures to abrupt changes in the oxygen supply. This should yield information regarding the behaviour of such cells as they circulate through areas of low and high oxygen availability in an industrial-scale bioreactor. It was found that a decoupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Step-change experiments in one reactor can be used to study dynamic effects of a sudden increase in glucose concentration or aerobic/anaerobic transitions [38,39]. A very rapid mixing of glucose can be obtained in a small STR.…”
Section: The Problem Of Gradientsmentioning
confidence: 99%
“…Step-change experiments in one reactor can be used to study dynamic effects of a sudden increase in glucose concentration or aerobic/anaerobic transitions [38,39]. A very rapid mixing of glucose can be obtained in a small STR.…”
Section: The Problem Of Gradientsmentioning
confidence: 99%
“…In spite of this shortcoming, the results obtained can be used to suggest what situations might be experienced by cells present at speci®c locations in a large-scale bioreactor. The more real case of the dynamic responses to¯uctuations in oxygen supply has been dealt with elsewhere [33]. Largescale fermentations [7] have shown that the dissolved oxygen concentration in a vessel¯uctuates with respect to time and increases appreciably at greater depths in the vessel as a result of hydrostatic pressure.…”
Section: Relevance Of Scale-down Results To Large-scale Bioreactorsmentioning
confidence: 99%
“…In reality individual cells are exposed tō uctuations in oxygen availability, which is why it is essential that measurements of the dynamic responses of cells to oxygen supply should be examined in order to achieve a deeper understanding. This topic is further developed by O'Beirne and Hamer [33].…”
Section: Discussionmentioning
confidence: 99%
“…DOC was monitored by a dissolved oxygen sensor (8) (Mettler Inpro 6800-Columbus, OH, USA) and controlled by a hybrid system composed by a PID controller and a fuzzy controller. The PID controller set agitation speed between 200 and 950 rpm (9). Gas flow rate was controlled by two flowmeters (10) (GFC AALBORG-Orangeburg, NY, USA).…”
Section: Bioreactor Experimental Set-upmentioning
confidence: 99%
“…At first, high oxygen availability can lead to a high biomass yield, with low acetate production. However, at a certain point, oxygen surplus becomes detrimental for the cultivation (decreasing both biomass yield and specific growth rate and increasing acetate production) [9][10][11]. Given the low solubility of oxygen in water and mechanical stirring limitations of the bioreactor (limited agitation speed to avoid shearing and limited oxygen delivered by the gas sparge), the dissolved oxygen control is highly nonlinear and represents a challenging control problem [12,13].…”
Section: Introductionmentioning
confidence: 99%